Pengaruh Pengungkapan Emisi Karbon, Ukuran Perusahaan, Profitabilitas, dan Leverage Terhadap Nilai Perusahaan: Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Energi yang Terdaftar di BEI Periode 2020 - 2022 - Shafa Mutiara Diva; Triyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the effect of disclosure of carbon emissions, company size, profitability, and leverage on firm value in energy subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022. The method used is multiple linear regression analysis with a sample of 42 observations from 14 companies that meet the criteria. The results showed that company size has a significant positive effect on firm value, while disclosure of carbon emissions, profitability, and leverage did not show a significant effect on firm value. This finding indicates that firm size has more influence on investors' decisions in assessing firm value, while other factors such as carbon emission disclosure, although important, have no significant effect in this context.